Design of Augmented Reality Integrated Learning Applications on Acid and Base Subject Material for F Phase Students - Rahmadani, Sri; Guspatni, Guspatni (Universitas Pendidikan Mandalika, 2023)
The aim of this research is to create integrated augmented reality learning media in the form of an application that focuses on the acid base material in the F phase or senior high school phase. Along with the development of the world of education, various kinds of new learning media have emerged. One of the interesting technologies that can currently be developed on Android is Augmented Reality (AR). Augmented Reality is considered one of the most advanced technologies in virtual reality research and is effective as a learning medium, especially chemistry. Augemented Reality is a technology that combines the real world with a computer-generated virtual world so that the boundaries between the two worlds are very minimal. Because of its advantages, AR can be used to create learning applications that can support the teaching and learning process. One lesson that can utilize this technology is chemistry learning about acids and bases. This application was created with Blender 3D software to create 3D acid base objects, Easy AR and Unity 3D to build applications. This media design was adopted by the Plomp development media. Where the design of this media is in accordance with the needs of schools which expect learning media to contain animation and be guided by questions that can guide students in discovering concepts. It is hoped that this learning application can be used at school and outside school as a support in learning chemistry, especially acids and bases.